ABO, Rh, and kell blood group antigen frequencies in blood donors at the tertiary care hospital of Northwestern India - Prinja, Nippun (Asian J Transfus Sci, 2020)
BACKGROUND: This study was performed to provide information on frequencies of ABO, Rh & Kell antigens/alleles, phenotype in blood donors at Blood Bank, SMS hospital, Jaipur and to compare them with other races. METHODOLOGY: This study was conducted on blood donors from April 2016 to March 2017 using a fully automated system for ABO,Rh & Kell typing of blood cells. D, C, c, E, e & K antigens were typed using monoclonal antisera from Immucor The data were collected and calculations done to determine the antigen/allele, phenotype. The chi square test 3 degree of freedom with P < 0.001 (S) was used for comparisons between the results of our study and those of other studies. RESULTS: A total of 8067 donors were included in this study. Maximum donors was of B blood group (39.4%) of age 18-25(35.5%) with 60-69kg weight (65%). The most common Rh antigen found was e(99.3%) followed by D (93.8%), C (85.4%), c (60.1%), E (17.5%). R1r (DCCee) was the most common phenotype in our study (39.5%). Kell (K+) antigen was present in 2.7% of donors. CONCLUSION: We have determined the prevalence of Rh antigens and Rh phenotypes in blood donor at our hospital and derived the allele frequencies in the same population.